Calculus : early transcendentals - Anton, Howard; Bivens, Irl; Davis, Stephen (John Wiley & Sons, 2013)
Anton, Bivens & Davis latest issue of Calculus Early Transcendentals Single Variable continues to build upon previous editions to fulfill the needs of a changing market by providing flexible solutions to teaching and learning needs of all kinds